Educação e cidadania na perspectiva da cidade educadora: uma proposta para Frederico Westphalen - Paetzold, Ophelia Sunpta Buzatto (Universidade do Vale do Rio do Sinos, 2006)
The present research, Education, Citizenship in prospect of the Educator City: A Proposal to Frederico Westphalen, objective to analyse and divulge the Educator City as a new dimension from Education and reflect the citizenship construction, like process that permits to the individual becomes himself citizen. To assure the education to everyone is to do social justice: garantee the right to have rights. Those premisses show the challenges that the school and ecucation face on the task to form citizens that in a proposal of Educator City, in a globalizated world, are or should be actors of social inclusion, emancipated participation, because they are able to articulated social groups to educative projects. In this acception, the education does not occur only in the formal education space, but it results from existenced experience in every spaces of the city by the union action from governmental organizations or do not. So, the public power and the society, in articulated form, exercise their educator functio
Keywords: cidade educadora; escola cidadã; infância; cidadania; childhood; educator city; citizenship; Ciências Humanas